Factors Impacting Invader-Mediated Recognition of Double-Stranded DNA - Caroline P. Shepard; Raymond G. Emehiser; Saswata Karmakar; Patrick J. Hrdlicka (Molecules, 2022)
The development of chemically modified oligonucleotides enabling robust, sequence-unrestricted recognition of complementary chromosomal DNA regions has been an aspirational goal for scientists for many decades. While several groove-binding or strand-invading probes have been developed towards this end, most enable recognition of DNA only under limited conditions (e.g., homopurine or short mixed-sequence targets, low ionic strength, fully modified probe strands). Invader probes, i.e., DNA duplexes modified with +1 interstrand zippers of intercalator-functionalized nucleotides, are predisposed to recognize DNA targets due to their labile nature and high affinity towards complementary DNA. Here, we set out to gain further insight into the design parameters that impact the thermal denaturation properties and binding affinities of Invader probes. Towards this end, ten Invader probes were designed, and their biophysical properties and binding to model DNA hairpins and chromosomal DNA targets were studied. A Spearman’s rank-order correlation analysis of various parameters was then performed. Densely modified Invader probes were found to result in efficient recognition of chromosomal DNA targets with excellent binding specificity in the context of denaturing or non-denaturing fluorescence in situ hybridization (FISH) experiments. The insight gained from the initial phase of this study informed subsequent probe optimization, which yielded constructs displaying improved recognition of chromosomal DNA targets. The findings from this study will facilitate the design of efficient Invader probes for applications in the life sciences.